Teacher quality and incentives theoretical and empirical effects of standards on teacher quality - Hendrik Juerges; Wolfram F. Richter; Kerstin Schneider (Center for Economic Studies and ifo Institute (CESifo), 2004)
Applying the theory of yardstick competition to the schooling system, we show that it is optimal to have central tests of student achievement and to engage in benchmarking because it raises the quality of teaching. This is true even if teachers? pay (defined in monetary terms) is not performance related. If teachers value reputation, and if teaching output is measured so that it becomes comparable, teachers will increase their effort. The theory is tested using the German PISA-E data. Our estimates suggest that, despite the flat career profile of German teachers, the quality of teaching tends to be higher in federal states with central exams.
Keywords: I28; 330; education; teacher quality; central examinations; yardstick competition; matching; Lehrkräfte; Dienstleistungsqualität; Leistungsanreiz; Yardstick Competition; Benchmarking; Bildungsniveau; Schätzung; Teilstaat; Schätzung; Deutschland; Zentralexamen; Zentralabitur; PISA <Test>